1994
DOI: 10.1007/bf00915736
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the visual outcome after cataract surgery

Abstract: Postoperative visual outcome and factors related to poor visual acuity three months after cataract surgery were evaluated in 243 cataract patients operated on at the Oulu University Hospital in 1990. The surgical technique used was a planned extracapsular cataract extraction with implantation of an intraocular lens (IOL) in 240 cases: a posterior chamber IOL in 231 cases and an anterior chamber IOL in 9 cases. The postoperative visual acuity was 0.5 or better in 74.5% of the eyes, 11.9% (29 eyes) had low visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Older patients lose a greater part of their remaining years. This could be a reason to operate older patients sooner, although the results of cataract extraction on the older patients are more often unsatisfactory (Lumme & Laatikainen 1993). On the other hand, for the younger patients surgery may help to preserve or return the working capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients lose a greater part of their remaining years. This could be a reason to operate older patients sooner, although the results of cataract extraction on the older patients are more often unsatisfactory (Lumme & Laatikainen 1993). On the other hand, for the younger patients surgery may help to preserve or return the working capacity.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are in accord with those the National Cataract Survey (UK) 9 16 but are rather lower than epidemiological prevalence data would suggest for this age group 1 2 and the figure of 33% of cataract cases with ARM identified in a study from Finland. 13 The proportion of eyes with severe (active or inactive exudative) ARM (2% or 0.2% of all notes reviewed) was also a great deal lower than epidemiological prevalence figures (5.2% 1 in those over 75 years and 7.4% in those over 85 years 22 ) and the same Finnish study (4.2%). 13 These findings suggest that our sample represents a selected population of patients with ARM, possibly reflecting diVering access to ophthalmic services (for example, primary carers may attribute poor vision to the presence of known ARM rather than to the development of a cataract) or diVering thresholds for, or expectations from, cataract surgery in patients with ARM (ophthalmologists may be reluctant to operate on those with ARM, particularly those with severe disease, on the grounds that they do not anticipate improvement in acuity).…”
mentioning
confidence: 85%
“…Although previous investigators have identified factors associated with poor outcome following cataract surgery, including the patient age and ocular co-morbidity (especially ARM), [9][10][11][12][13][14][15][16] none has addressed specifically the benefits of surgery in these high risk groups.…”
mentioning
confidence: 99%
“…In recent years, the number of people who undergo cataract surgery has increased rapidly and it becomes the most frequently performed cost-effective surgical procedure throughout the world. [4][5][6] The outcome of cataract surgery for an individual or for a defined population is therefore as important as measuring the quantity of surgical operations performed. The outcome of cataract surgery can be measured through postoperative level of visual acuity, ability to function, quality of life, and economic rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Previous studies have shown that surgically induced uncorrected refractive error was the most common cause of poor visual outcome after operation. 20 Overall, this study implicates that greater effort should be exerted to identify the main cause of visual impairment after operation and to devise strategies so as to maximize the level of visual outcome.…”
mentioning
confidence: 99%